Study of Five Clones with Combinations of Growth Regulators Based on Growth and Anatomical Characteristics of Rubber Plant (Hevea brasiliensis L.) - Try Koryati; Wiwik Yunidawati; Radite Tistama; Nurhayati Nurhayati; Mazlina Mazlina; Rosmaiti Rosmaiti (AGRIVITA, Journal of Agricultural Science, 2023)
As an export commodity, rubber is a major contributor to Indonesia's foreign exchange. Regarding the increase in rubber production, a study on combinations of growth regulators and rubber clones has been carried out based on plant growth and anatomical characteristics during the immature plant period. This research is conducted for eighteen months at the KSO Karang Inong plantations, PTPN-I, and PTPN-III, East Aceh District, using five clones. This study adopts a nested design with three factors: clones, Growth Regulators (GRs), and paclobutrazol. The clones used are PB 260, IRR 104, IRR 112, IRR 39, and 105. The GRs combination factor between IAA and Kinetin consists of seven levels and three levels of paclobutrazol. The results show that the rubber clones PB260 and IRR105 give higher stem girth and plant height than the other clones when applied with GRs at six different levels. The most expansive leaf area is found in clone IRR 104 compared to other clones. In addition, paclobutrazol affects plant height. Applying paclobutrazol can reduce plant height for all clones but increases stem girth, skin thickness, number and diameter of latex vessels, and total chlorophyll at 46 months after treatment.